PENDIDIKAN KESEHATAN TENTANG PERSONAL HYGIENE PADA IBU NIFAS DI RUANG ASTER RSU KABUPATEN TANGERANG - Ratnasari, Febi; Lubis, Maulinda Sadari; Febriliyani, Afelia; Ali, Afri Satriawan; Firman, Agus; Handika, Aisah; Fuadi, Allif; Fauziah, Anisya Nur (Nusantara Hasana Journal, 2022)
The postpartum period is the period after childbirth and the birth of the baby, the placenta and the membranes needed to restore the uterine organs as before pregnancy with a time of approximately 6 weeks. The postpartum period (puerperiem), which comes from the Latin puer which means baby and partus which means giving birth or means the period after giving birth. This research to determine the implementation and increase the knowledge of patients and families about vulvar care and personal hygiene in postpartum women at the Tangerang Regency General Hospital. This type of research is descriptive using qualitative research methods. In-depth interviews were carried out on 4 respondents and the lecture method was carried out, observing the implementation in the Aster room. The implementation of Personal Hygiene at the Tangerang District Hospital in terms of structure, process and output is carried out quite well both in spontaneous labor and in post-cesarean delivery.